Datações de radiocarbono relacionadas com o património arqueonáutico em Portugal - Alves, Francisco J. S.; Soares, António M. Monge; Cabral, João M. Peixoto; Mário Varela, Mário; Ribeiro, Maria Isabel M. (Trabalhos de Antropologia e Etnologia, 2020)
.